Kontribusi UMKM Terhadap Perekonomian Indonesia Serta Peluang dan Tantangan dalam Era Digitalisasi - Delfiana Jesika Dwifanty; Jordan N. Leobisa; Angelina Aldensia Bernoli; Enike Tje Yustin Dima (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors that have an important role in supporting Indonesia's national economy. Its contribution is enormous to the Gross Domestic Product (GDP), job creation, and increased innovation, especially in the face of global economic challenges and social inequality. This research aims to examine in depth the role of MSMEs in encouraging Indonesia's economic growth and identify various challenges faced by this sector. The method used in this study is library research, by analyzing various sources of scientific literature, policy reports, and relevant empirical data related to the role of MSMEs. The results of the study show that MSMEs not only contribute to increasing national GDP, but also become the main driving force in providing jobs for the community, especially in rural and suburban areas. In addition, MSMEs are also an important means in the development of local innovation, especially in the use of simple technology that is in accordance with community conditions. However, MSMEs also face a number of serious challenges that can hinder their contribution to economic growth. These challenges include limited access to digital payment systems, low quality of human resources (HR), weak marketing networks, and limited capital and technology. Thus, to increase the role of MSMEs in national economic development, synergy is needed between the government, the private sector, and financial institutions in providing comprehensive and sustainable support. The support includes training on human resource capacity building, access to capital, digital transformation, and strengthening the business ecosystem. This research is expected to contribute to the development of policies that favor the empowerment of MSMEs in Indonesia.